Systems approaches to correlates of protection and progression to TB disease. (October 2018) - Fletcher, Helen A.
Highlights: Accurate TB diagnosis, capacity for large scale immune sample collection and advances in systems technologies have enabled rapid advances in immune correlates studies. We do not have an immune correlate of protection (CoP) for a TB vaccine as there have been no TB vaccine trials with both efficacy and sample availability for such an analysis to be performed. New TB vaccine efficacy trials with disease and infection endpoints will provide future opportunities for immune CoP analysis. Vaccine efficacy trials and observational studies in populations at high risk of TB disease have enabled the identification of Correlates or Risk (CoR) of progression to TB Correlates of risk analysis using whole systems approaches provide deeper insight into mechanisms of immune protection and lead to the development of new and better interventions for TB disease. Abstract: Tuberculosis (TB) is the leading cause of death due to a single infectious disease and an effective vaccine would substantially accelerate global efforts to control TB. An immune correlate of protection (CoP) from TB disease could aid vaccine optimization and licensure. This paper summarises opportunities for identifying CoP and highlights results from correlates of risk studies. Although we don't have CoP, there are ongoing efficacy trials with both disease and infection endpoints which provide opportunities for such an analysis. Transcriptomics has successfully identified robust CoR, with transcripts found in the Type I IFN pathway. Correlates of lower risk include BCG antigen specific IFN-γ and natural killer cells. Collating evidence from multiple studies using a range of systems approaches supports a role for IFN-γ in protection from TB disease. In addition, the cells that express the IFN-γ receptor are also important in protective immunity. Protection is a culmination not only of the amount of IFN-γ produced by T cells and NK cells but by the ability of IFN-γ receptor expressing monocytes to respond to IFN-γ. To better understand IFN-γ as a correlate we need to understand host-factors such as age, sex, co-infection, nutritional status and stress which may alter or impair the ability of cells to respond to IFN-γ. These studies highlight recent advances in our understanding of the immune mechanisms of TB disease risk and show the importance of whole systems approaches to correlates of risk analysis. CoP may be useful tools for specific vaccine products in specific populations, but a well-designed CoR analysis can identify novel immune mechanisms and provide insights critical for the development of new and better TB vaccines.